2020
DOI: 10.1002/ppap.202000180
|View full text |Cite
|
Sign up to set email alerts
|

Cold atmospheric plasma jet array for transdermal drug delivery

Abstract: Transdermal drug delivery (TDD) is an important drug delivery method, and cold atmospheric plasma has been proven its potential as a TDD approach. In this study, a 9-channel plasma jet array was designed to enhance TDD efficiency. The Franz diffusion experiment showed that the TDD efficiency of the drug across the skin was enhanced about 2-110 times after the plasma jet array treatment. The histological analysis showed that the structure of the stratum corneum could be destroyed by the plasma. Further investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…A previous study has shown that a 0.5% oxygen mixture in the working gas can promote TDD significantly. [14] Therefore, in this study, the working gas of the DC helium and DBD helium plasma jet were all mixed with 0.5% oxygen. It needs to be mentioned that when a study on the discharge mode, the indium tin oxide (ITO) glass was used instead of the skin of which the conductive side was grounded and in contact with plasmas.…”
Section: Touchable Plasma Device Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study has shown that a 0.5% oxygen mixture in the working gas can promote TDD significantly. [14] Therefore, in this study, the working gas of the DC helium and DBD helium plasma jet were all mixed with 0.5% oxygen. It needs to be mentioned that when a study on the discharge mode, the indium tin oxide (ITO) glass was used instead of the skin of which the conductive side was grounded and in contact with plasmas.…”
Section: Touchable Plasma Device Setupmentioning
confidence: 99%
“…[8] Cold atmospheric plasma for TDD has attracted much attention in recent years due to its advantages such as high chemical activity, painlessness, noninvasive, low cost, and so on. [9] Different plasma sources were used for TDD, such as argon plasma jet, [10] microplasma, [11] air dielectric barrier discharge (DBD) plasma, [12,13] and helium plasma jet array, [14] and these have confirmed the possibility of plasma-enhanced TDD. Research on molecular dynamics has also made progress.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17] In addition, a strong electric field, up to 100 kV/cm, is generated when the CAP sources come into contact with a dielectric target, which induces electroporation (EP) in cell membranes. [18][19][20] The EP of cell membranes refers to the changes in the relevant mechanical properties of cell membranes under a large electric field, resulting in the formation of holes through the cell membrane and leading to the transmembrane movement of extracellular molecules. [21,22] The cancer cell membrane EP destroys the cell membrane integrity and changes the cell membrane permeability, [23,24] which is one of the conditions for the transport of CAP RONS across membranes and their accumulation in cancer cells.…”
mentioning
confidence: 99%
“…[13] The processed region is discontinuous for APPJ-array due to the discrete plasma plume. [14][15][16] Floating electrode dielectric barrier discharge (FEDBD) is another type of cold plasma source that could treat an object with a relatively large area. [17] However, the object to be treated needs to be placed close to the high-voltage electrode since the treating object works as the grounding electrode, and the surface of the object should be flat enough to generate even discharge.…”
mentioning
confidence: 99%